IDENTIFICATION OF DENTAL AND ORAL DISEASES IN HUMANS USING BAYES THEOREM METHOD - Purnomo, Nopi; Wardana, Bendra; Yuliana, Devi; Rasyid, M. (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Teeth are part of the chewing apparatus in the digestive system in the human body, so they indirectly play a role in the health status of individuals. The mouth is an ideal place for bacteria to multiply due to temperature and humidity. There are several tooth fissures in the mouth so that food residues are easily left behind. Teeth and mouth are very important organs of the body because all diseases will start from diseases in this organ will cause several dangerous diseases that attack other organs of the body. This system was built with the aim of making it easier to identify Dental and Oral Cavity Diseases and producing the highest accuracy in diagnosing these diseases. The expert system was built using the Bayesian theorem method which is the main technique in the process of detecting dental and oral cavity diseases based on the knowledge of an expert. Diagnostic test results with an accuracy level of 61%, Therefore, the research conducted can be said to be successful in diagnosing dental and oral cavity diseases. Keywords: Expert Systems, Identification, Teeth and Oral Cavity, Bayes Theorem. Abstrak: Gigi merupakan bagian dari alat pengunyahan pada sistem pencernaan dalam tubuh manusia, sehingga secara tidak langsung berperan dalam status kesehatan perorangan. Mulut merupakan suatu tempat yang sangat ideal bagi perkembangbiakan bakteri karena temperatur dan kelembaban. Terdapat beberapa fisur gigi di mulut sehingga sisa makanan mudah tertinggal. Gigi dan mulut adalah organ-organ tubuh yang sangat penting karena semua penyakit akan berawal dari penyakit pada organ ini akan menimbulkan beberapa penyakit-penyakit membahayakan yang menyerang organ tubuh lainnya. Sistem ini dibangun dengan tujuan untuk mempermudah mengidentifikasi Penyakit Gigi dan Rongga Mulut serta menghasilkan keakuratan tertinggi dalam diagnosis penyakit tersebut. Sistem pakar yang dibangun menggunakan metode teorema bayes yang merupakan teknik utama dalam proses mendeteksi penyakit Gigi dan Rongga Mulut berdasarkan pengetahuan dari seorang pakar. Hasil pengujian diagnosis dengan tingkat akurasi sebesar 61%, maka dari itu penelitian yang dilakukan ini dapat dikatakan berhasil dalam mendiagnosa penyakit Gigi dan Rongga Mulut. Kata kunci: Sistem Pakar, Identifikasi, Gigi dan Rongga Mulut, Teorema Bayes.